Stakeholder relationships and corporate social goal orientation: Implications for entrepreneurial psychology - Lu, Xiaowei; Sheng, Ya; Xiao, Yao; Wang, Wei (Frontiers in Psychology, 2022)
As the sensitivity to corporate social responsibility (CSR) continues to grow, the goal of enterprises has expanded beyond the sole pursuit of economic value. Corporate social goal orientation has therefore come to occupy a central position in entrepreneurs’ psychology and the transition away from a market-only economy. This study uses secondary data from 4288 samples of 725 Chinese-listed companies from 2009 to 2020 to explore the driving factors in social goal orientation based on the characteristics of sample companies and their industry groups from the perspective of stakeholder relationships. The results can be summarized as follows. (1) There is an inverted U-shaped relationship between government stakeholder relationships and social goal orientation, and there is a significantly positive relationship between financial stakeholder relationships, market stakeholder relationships, and corporate social goal orientation. (2) The correlation between single-dual stakeholder relationships and social goal orientation is not consistent. In light of the nature of the roles of government and the market, the correlation between the government–market dual relationship and corporate social goal orientation is not significant. However, there is a significant correlation between the finance–government dual stakeholder relationship and social goal orientation; that is, the dual stakeholder relationship maintains the existence of non-institutional capital and corporate financial capital. Moreover, there is no significant correlation between the market–finance dual relationship and corporate social goal orientation, and there is substitutability between market and financial stakeholder relationships. With the deepening of our understanding of corporate social responsibility, the core goal of enterprises is no longer confined to the pursuit of economic value, and their social goal orientation has come to be regarded as a major driving force in sustainable development. This study enriches the research on the relationship between stakeholder relationships and shows that stakeholder relationships also have important significance to both achieving corporate goals and shaping entrepreneurs’ psychology.